Short Communication: Using wildlife for local livelihood – Experiences from the Bird’s Head Peninsula, West Papua, Indonesia - FREDDY PATTISELANNO; JOHN R.M. APITULEY; AGUSTINA Y.S. AROBAYA; JOHAN F KOIBUR (Society for Indonesian Biodiversity, 2019)
Abstract. Pattiselanno F, Apituley JRM, Arobaya AYS, Koibur JF. 2019. Short Communication: Using wildlife for local livelihood – Experiences from the Bird’s Head Peninsula, West Papua, Indonesia. Biodiversitas 20: 1839-1845. Wildlife products are valuable commodities, and wild meat is considered as premium value because it has a high value per unit weight compared with other forest products Wildlife products are commonly used for consumption purpose, generating household income and cultural reasons. Because cultural values differ among ethnic groups, it is important to understand how wildlife contributes to local livelihoods in different areas of the Bird’s Head Peninsula. Data was obtained opportunistically during fieldwork to different parts of West Papua Province from 2010 to 2018. Study sites were not intentionally selected, but they were considered during the involvement of authors in research and survey across the Bird’s Head Peninsula of West Papua Province Data was collected through indirect observation and semi-structural interviews. A literature review was also completed to supplement the primary data collected from the fieldwork. The results indicated many people rely on wild meat as an alternative source of food for the household. Wildlife also offered forms of income generation such as sale of bushmeat products. Acquisition of animal parts as cultural artifacts, for personal adornment or for trophies was still a widespread practice throughout the areas. Religious and cultural aspects also contributed significantly to the use of wild meat for traditional or spiritual aspects as well. Finally, some reasons have been identified that derive peoples’ attitudes in using wildlife across the Bird’s Head Peninsula, and they are for consumption, sale and the relationship between wild animal species and cultural values.